SYSTEM OF STUDENT CLUB ASSOCIATIONS IN THE EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY - L. Saenko; L. Kuvaeva (Вестник Северо-Кавказского федерального университета)
The article presents the analysis and highlights the essential content of the concept of "student club" ("student club association"). The main directions of student clubs activity in the university are presented. The contradictions and problems of the activity of student club associations in educational organizations are revealed. The activity and features of the functioning of student club associations in Russia and abroad are considered. The results of a survey of students regarding their participation / non-participation in student club associations are presented. The authors come to the conclusion that student club as the form of organization of educational work is the basis for the socio-cultural and professional development of youth.